Heavy-Metal-Resistant Microorganisms in Deep-Sea Sediments Disturbed by Mining Activity: An Application Toward the Development of Experimental in vitro Systems - Gillard, Benjamin; Chatzievangelou, Damianos; Thomsen, Laurenz; Ullrich, Matthias S. (Frontiers in Marine Science, 2019)
Future mining of polymetallic nodules in the Clarion Clipperton Fracture Zone (Northeastern Pacific) is expected to affect all benthic ecosystems. The diversity, distribution, and environmental functions of microorganisms inhabiting abyssal sediments are barely understood. To understand the ​consequences of deep-sea mining, experimental in vitro systems needs to be established to test hypotheses on the environmental impact of mining. For this, 40 bacterial strains, belonging to proteobacteria, actinobacteria and firmicutes were isolated from deep-sea sediments and nodules sampled at depths of  4000 m. Phenotypic characterization revealed a strong inter-species and moderate intra-species variability. Determination of minimum inhibitory concentrations indicated the presence of acute manganese-resistant bacteria such as Rhodococcus erythropolis [228.9 mM], Loktanella cinnabarina [57.2 mM], and Dietzia maris [14.3 mM] that might be suitable systems for testing the effects of release of microbes from nodules and their interactions with sediment particles in plumes generated during mining. Comparative genomic analysis indicated the presence of manganese efflux systems relevant for future transcriptomics or proteomics approaches with environmental samples and might serves in paving the way to develop model systems including representative organisms which are currently not cultivable. Monitoring deep-sea mining activity at abyssal depth is a challenge that has to be tackled. We proposed the use of API strips as a fast-on-board methodology for bacterial monitoring as an indicator for sediment plume dispersions within the water column.